Implementasi AI “Typing Speed Test” untuk membantu guru meningkatkan kemampuan mengetik siswa manajemen perkantoran - Dharma, Buyung Adi; Basuki, Andi; Churiyah, Madziatul; Sakdiyyah, Dewi Ayu (Penamas: Journal of Community Service, 2024)
This service aims to improve digital teacher literacy through intensive training so that they can effectively implement the "Typing Speed Test" application in learning. This service activity was carried out using the Participatory Action Research (PAR) approach. The results of the service showed a significant increase in digital teacher literacy and students' typing skills. Teachers involved in the training were able to master and utilize the "Typing Speed Test" application well in the learning process. In addition, students who took part in this application-based learning showed a real increase in typing speed and precision, which contributed to their readiness to face the demands of an increasingly competitive world of work. This success emphasizes the importance of teacher training before implementing new technologies in learning. With an interactive and data-driven approach, this service program not only improves students' technical skills but also equips teachers with effective strategies to support student development in the digital era.